Kolom Selasaan as Community Religious Traditions in The Context of Fostering Religious Improvement of The Akkor Village Community With a Participatory Action Reserch (PAR) - Mahbubah, Latifatul; Muslih, Muslih; Muhlis, Achmad (Proceedings of Annual Conference on Community Engagement, 2022)
Kolom Selasaan is a routine activity carried out every Tuesday night by the men of the Akkor Village community. This activity is led by kiyai and leaders in the local village and is filled with various activities such as tahlil and studying fiqh books. The purpose of the implementation of this activity is to improve and increase public understanding about the implementation of worship, especially for young people who do not go to school in Islamic boarding schools. Through this training, the community gets additional lessons and knowledge that can be used as a reference in improving the quality of their worship and religion, which they have never received considering that they have never studied religion in detail and in depth. Akkor Village is located in Palengaan District, Pamekasan Regency with a population of more than four thousand people. The community in this village used to have a tradition of sending children to Islamic boarding schools from an early age, but over time this tradition began to erode, resulting in reduced public understanding of religious matters. So seeing from this situation the community service group took the initiative to provide religious improvement guidance which was packaged in the form of a "Kolom Selasaan". This study uses a Participatory Action Research (PAR) approach considering that in its implementation it requires active participation from the community to encourage changes for the better as expected.